Using Free-Comment with consumers to obtain temporal sensory descriptions of products. (December 2020) - Mahieu, Benjamin; Visalli, Michel; Thomas, Arnaud; Schlich, Pascal
Highlights: A new temporal method not based on a predefined list of descriptors is introduced. Temporal Free-Comment data can be obtained from consumers at home. The data can be analysed product-wise and period-wise. Temporal discrimination and characterization of the products were highlighted. Abstract: Temporal Dominance of Sensations (TDS) and Temporal-Check-All-That-Apply (TCATA) are the most popular methods used with consumers for the temporal sensory characterization of a set of products. However, TDS and TCATA share the same limitation: they rely on a predefined and necessarily short list of descriptors. Free-Comment (FC) enables the sensory characterization of a set of products freed of any issue induced by the use of a list of descriptors, but for practical reasons collecting FC descriptions concurrently to the product intake is nearly impossible. Attack-Evolution-Finish (AEF) is an alternative to TDS and TCATA that replace concurrent by retrospective data collection. In AEF, subjects are asked to choose in a list one descriptor for each of the so-called periods: Attack, Evolution, and Finish. The paper introduced Free-Comment Attack-Evolution-Finish (FC-AEF) to extend FC to temporal sensory analysis where descriptor selections of AEF are replaced by FC descriptions. FC-AEF has been used at home with 63 consumers having tasted five dark chocolates. The data were analysed product-wise and period-wise and showed that FC-AEF enabled to provide temporal discrimination and characterization of the products. The product-wise analyses identified in each period the descriptors of each product enabling this discrimination. The period-wise analyses identified for each product the descriptors generating a temporal kinetic of its perception.